Midlife crisis perceptions, experiences, help-seeking, and needs among multi-ethnic Malaysian women - Wong, L.P.; Awang, H.; Jani, R. (2012)
In the present study, researchers explored attitudes toward midlife crises, experience with midlife crises, help-seeking, and needs among multi-ethnic Malaysian women. A total of 14 focus group discussions were conducted with 89 Malaysian women of different ages and socioeconomic backgrounds. Women expressed concern over physical aging and decline in their physical functional health. Having a midlife crisis was frequently reported. Issues that were frequently reported to trigger a midlife crisis, such as empty nest syndrome, impact of aging on sexual and reproductive function, extended parenthood, caring for aging or ill parents, and career challenges were noted by the study participants (listed here in order of most to least frequently reporting of these themes across the group discussions). Overall, these issues were associated with attitudes about aging. A comparatively less open attitude toward sexual attitudes and help-seeking for sexual problems were found among the Malay and Indian women. This may imply that intervention to increase positive attitudes concerning both sexuality and help-seeking intentions should be culturally specific. The use of religious coping for comfort and consolation was frequently reported; therefore, those providing midlife crisis prevention and intervention programs should consider involving faith-based interventions in the Malaysian setting.